Bhāratīya vaijñānika : ādhunika Bhārata ke 12 śreshṭha vaijñānikoṃ kī sacitra jīvaniyām, vijñāna sādhanā, anveshaṇa aura āvishkaroṃ kā prāmāṇika varṇana - Kapūra, Śyāmanārāyaṇa, 1908- (SAMP early 20th-century Indian books project, 1942)
On the achievement and works of modern Indian scientists.